Contributions of playground singing games to the social inclusion of refugee and newly arrived immigrant children in Australia - Marsh, K; Dieckmann, S (Taylor and Francis, 2017)
In recent decades, researchers from the fields of music education, ethnomusicology, folklore and sociology have developed an increasing interest in children’s musical play traditions and the ways in which children teach and learn, perform, create and transform playground games and songs. Such repertoire is drawn both from oral traditions and from children’s mediated environments, and has formed the basis of a number of prominent pedagogical approaches to music education. As malleable forms of musical expression and social activity that are found worldwide both outside of and within school contexts, playground games provide a mechanism for the growing numbers of refugee and newly arrived migrant children to attain social inclusion within school environments in host countries, while retaining connections with home cultures. This paper discusses refugee and newly arrived immigrant children’s engagement in and uses of playground musical play in a primary school in Sydney, Australia and the game characteristics that contribute to their socially integrative potential.